Effects of low temperature pretreatment of germinated seeds on floral bud differentiation and plant growth in radish (Raphanus sativus L) - WANG Bing-liang; DENG Jian-ying; ZENG Guang-wen (浙江大学学报. 农业与生命科学版)
In order to study the effects of low temperature treatment on the floral differentiation and plant growth, germinated radish (Raphanus sativus L.) seeds of the winter variety ‘Yi-Dian-Hong’ and the spring variety ‘Duan-Ye 13’ were subjected to 5℃ or 10℃ for 10 to 40 days, the control seedlings of both cultivars were germinated at 25℃ and didn't subject to low temperature. After low temperature treatment, all seedlings, including the control, were transplanted into glasshouse with a warm (>15 ℃) and long photoperiod (16 h) growth condition. It was found that floral bud differentiation of both radish varieties were promoted by low temperature pretreatment. The promoting effects were better when the germinated seeds were subjected to lower temperature and/or for longer treatment duration. Only 10-day pretreatment of germinated seeds at 5℃ or 10℃ was enough to enhance the floral bud differentiation in the spring variety ‘Duan-Ye 13’, whereas at least 20-day pretreatment was required for the promotion of floral bud differentiation in the winter variety ‘Yi-Dian-Hong’. On the other hand, low temperature pretreatment of germinated seeds inhibited the plant growth, including plant height, number of leaves as well as leaf length and width. The longer the treatment duration was, the stronger the inhibitions were.